Genetic stability of RSV-F expression and the restricted growth phenotype of a live attenuated PIV3 vectored RSV vaccine candidate (MEDI-534) following restrictive growth in human lung cells - Nelson, Christine L.; Tang, Roderick S.; Stillman, Elizabeth A. (Vaccine, 2013)
•MRC-5 cells provided restrictive growth environment for RSV vaccine candidate.•Evaluated stability of RSV-F expression and maintenance of attenuation phenotype.•Minor decline in attenuation and RSV-F expression after 23 passages in MRC-5 cells.•Modified virus still able to elicit protective anti-RSV immune responses in hamsters. MEDI-534 is the first live, attenuated and vectored respiratory syncytial virus (RSV) vaccine to be evaluated in seronegative children. It consists of a bovine/human parainfluenza virus type 3 (PIV3) backbone with the RSV fusion glycoprotein (RSV-F) expressed from the second position. The PIV3 fusion and hemaglutinin-neuraminidase proteins are human-derived. No small animal appropriately replicates the restrictive growth of bovine PIV3 (bPIV3) based viruses relative to human PIV3 (hPIV3) observed in the respiratory tract of rhesus monkeys and humans, making analysis of the genetic stability of the attenuation phenotype and maintenance of RSV-F expression difficult. Screening of multiple cell-lines identified MRC-5 cells as supporting permissive growth of hPIV3 while restricting bPIV3 and MEDI-534 growth. In MRC-5 cells, the peak titers of MEDI-534 were more than 20-fold lower compared to hPIV3 peak titers. After more than 10 multicycle passages in MRC-5 cells, genetic alterations were detected in MEDI-534 that contributed to a partial loss in restricted growth in MRC-5 cells and a decrease in RSV-F expression. These adaptive mutations did not occur in the RSV-F gene but were found in the polyA sequence upstream of the transgene. MRC-5 adapted MEDI-534 viruses (1) lost some attenuation but did not replicate to the level of hPIV3 in this cell line, (2) did not completely lose RSV-F expression and (3) were able to elicit a protective anti-RSV immune response in hamsters despite lower levels of RSV-F expression. Interestingly analysis of shed MEDI-534 from a recent clinical trial indicates that in some recipients similar mutations arise by day 7 or day 12 post immunization (in press) suggesting that these mutations can arise rapidly in the human host. The utility and limits of MRC-5 cells for characterizing the attenuation and RSV-F expression of MEDI-534 is discussed.